Examen especial al área de talento humano de la cooperativa de ahorro y crédito Pequeña Empresa Pastaza, 2023. - Tenorio Guambo, Leandro Ricardo (2025)
This research aims to conduct a special audit of the Human Talent department of the Pequeña Empresa Pastaza Savings and Credit Cooperative for the fiscal year 2023. Since its founding in 1987, this institution has played a key role in Ecuador’s popular and solidarity-based financial sector. However, it currently faces significant challenges in human resource management, particularly in areas such as outdated job manuals, irregular performance evaluations, limited internal communication, and weaknesses in hiring processes. The study followed a qualitative and descriptive approach, applying techniques such as direct observation, interviews, and document analysis. The evaluation was carried out based on the COSO III framework and International Auditing Standards, focusing on five internal control components: control environment, risk assessment, control activities, information and communication, and monitoring. Key findings revealed outdated documentation, incomplete internal audits, and the lack of key performance indicators to assess recruitment efficiency. Despite these issues, the internal control system achieved a confidence level of 85%, with a moderate risk level of15%. As a result, corrective actions are recommended to improve human talent management. These include updating normative documents, implementing performance indicators, strengthening institutional communication, and conducting comprehensive internal audits. This work contributes to strategic decision-making and promotes a more efficient and sustainable human resource management system aligned with the cooperative’s institutional goals.